Determinant Factors for Achieving Sustainable Development in Jambi Province: Determinant Factors for Achieving Sustainable Development in Jambi Province - Astuti, Camelia Puji; Hamzah, Muhammad Zilal; Sofilda, Eleonora (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The Human Development Index (HDI) and the poverty line are important indicators in measuring community welfare and are in line with the Sustainable Development Goals (SDGs) initiated by the United Nations (UN). Jambi Province is one of the provinces that has an average HDI below the national average with a high poverty rate. The purpose of this study was to analyze and examine the determinants of the HDI and Poverty Line in Jambi Province. The method used is a qualitative approach using SLR bibliometrics and a quantitative approach with panel data in 11 districts/cities in Jambi Province with a research year of 2017-2023. The results of the qualitative approach show that the productivity of literature related to the Human Development Index (HDI) and Poverty fluctuated during 2021-2024 with the highest growth in 2023 and 2024. The results of the quantitative approach show that all independent variables have a significant effect on the Human Development Index (HDI). Meanwhile, only the education budget and Regional Independence Index variables do not have a significant effect on the poverty line. Recommendations based on research results, the Central Government and Jambi Province need to encourage inclusive economic growth to accelerate the improvement of social welfare, need to strengthen sustainability-based village development programs to improve the quality of life of the community. The government needs to strengthen regional financial management mechanisms to ensure more efficient and effective public spending that has an impact on community welfare so that the achievement of SDGs can be realized in 2030.